Early history of operative treatment of patellar fractures - Bartoníček, Jan; Rammelt, Stefan (International orthopaedics, 2015)
The presented overview shows that the first efforts to address patellar fractures by operative treatment, although sporadic, emerged in the pre-antiseptic era. Introduction of Lister's antiseptic method in Great Britain, Germany and the USA in 1877-1882 contributed to a new, progressive trend in the treatment of fractures of the patella as well as of other bones. The authors, using Lister's antiseptic method, evaluated three basic aspects in their operations, namely healing of the surgical wound without infective complications, achievement of bony union and a good functional outcome, i.e. restoring the range of motion in the knee, even if limited in most cases. The majority of them used a longitudinal incision and fixation by a silver wire.
Keywords: United States; Patella; patela; fraktury kostí; vnitřní fixace fraktury; lidé; Europe; History of orthopaedics; Patellar fractures; Evropa; dějiny 19. století; Spojené státy americké; Fractures, Bone; History of internal fixation; Fracture Fixation, Internal; History, 19th Century; Humans